Bagriy O.V. Equations of a plane problem for the environment with substantial internal Coulomb friction - Багрій, О. В. (Problems of Tribology, 2018)
A plane problem for an environment with a substantial internal coulomb friction is formulated as a boundary value problem for a planar inhomogeneous physically nonlinear region filled with a material material whose deformations of shaping are significantly affected by the compressive stresses. In the mathematical formulation of the problem, in addition to the known equations of equilibrium and continuity of deformations, specific physical equations are used in which variable parameters are introduced instead of elastic constants, which depend on the values of stresses and deformations achieved at each stage.